2001
DOI: 10.1007/s004250000486
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation in photosynthesis: Does the quenching of chlorophyll fluorescence originate from antenna complexes of photosystem II or from the reaction center?

Abstract: Dissipation of light energy was studied in the moss Rhytidiadelphus squarrosus (Hedw.) Warnst., and in leaves of Spinacia oleracea L. and Arabidopsis thaliana (L.) Heynh., using chlorophyll fluorescence as an indicator reaction. Maximum chlorophyll fluorescence of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU)-treated spinach leaves, as produced by saturating light and studied between and -20 degrees C, revealed an activation energy delta E of 0.11 eV. As this suggested recombination fluorescence produced by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 32 publications
6
61
0
1
Order By: Relevance
“…It has been suggested that high q O in relation to q N is an indicator for high q O (Bukhov et al, 2001;Sane et al, 2003). We found q O /q N Figure 7.…”
Section: Dissipation Of Excess Energy Depends On the Aggregation Statsupporting
confidence: 49%
“…It has been suggested that high q O in relation to q N is an indicator for high q O (Bukhov et al, 2001;Sane et al, 2003). We found q O /q N Figure 7.…”
Section: Dissipation Of Excess Energy Depends On the Aggregation Statsupporting
confidence: 49%
“…It has been previously hypothesized that the potential for non-photochemical quenching of PSII reaction centers might protect against excess light (10). More recently the reduction of Q A has been suggested as a major requirement for efficient reaction center quenching (43). It has been implied also that the increased population of Q A Ϫ may enhance the dissipation of excess light energy within the PSII reaction center during cold acclimation via its back non-radiative reaction with P680 ϩ , thus complementing the capacity for zeaxanthin cycle-dependent energy quenching (44).…”
Section: Discussionmentioning
confidence: 99%
“…Quenching based in the PSII reaction center (as opposed to LHC antenna) has also been observed in higher plants (Bukhov et al 2001;Stroch et al 2004) and green microalgae (Finazzi et al 2004), and possibly in diatoms (Eisenstadt et al 2008). Appearance of reaction centre quenching depends on the balance between light and carbon fixation fluxes (Finazzi et al 2004) along with a clear temperature influence (Kornyeyev et al 2004).…”
Section: Effect Of Light Stress On Fluorescence Signatures and Their mentioning
confidence: 93%
“…In contrast to the antennabased quenching, it cannot cause changes in the F o level (Maxwell and Johnson 2000). Nevertheless, as well as the antenna-based quenching it requires thylakoid acidification, but it does not require deepoxidized xanthophylls (Bukhov et al 2001;Finazzi et al 2004). The qI part of this reaction center based quenching is associated with a reversible inactivation of a sub-population of the PSII (Finazzi et al 2004) as well as with PSII photodamage (Kornyeyev et al 2004).…”
Section: Effect Of Light Stress On Fluorescence Signatures and Their mentioning
confidence: 99%